LINC00858 promotes colon cancer progression through activation of STAT3/5 signaling by recruiting transcription factor RAD21 to upregulate PCNP - Ting Xu; Kun Wu; Jin Shi; Lindong Ji; Xudong Song; Guoquan Tao; Shutao Zheng; Li Zhang; Baofei Jiang (Cell Death Discovery, 2022)
Abstract The purpose of our investigation is to explore the putative molecular mechanisms underpinning LINC00858 involvement in colon cancer. The expression of LINC00858 in TCGA data was identified using the GEPIA website. Colon cancer cancerous tissues were clinically collected. The expression of LINC00858, RAD21, and PCNP in colon tissues or cells was determined using RT-qPCR. The interactions among LINC00858, RAD21, and PCNP promoter region were determined by means of RNA pull down, RIP, and ChIP assays. Cell proliferative, apoptotic, invasive, and migrated capabilities were evaluated. Western blot was conducted to determine RAD21, PCNP, phosphorylated (p)-STAT3, STAT3, p-STAT5 and STAT5 and apoptosis related proteins. A nude mouse model of colon cancer was constructed and tumorigenesis of colon cancer cells was observed. LINC00858 was upregulated in cancerous tissues and cells. LINC00858 recruited the transcription factor RAD21. Overexpression of LINC00858 promoted the binding of RAD21 and PCNP promoter region, which increased the expression of PCNP. Silencing of RAD21 or PCNP reversed the promoting effect of LINC00858 on the disease initiation and development. PCNP silencing inhibited proliferative ability and promoted apoptotic ability of cancerous cells via STAT3/5 inhibition, which was reversed by colivelin-activated STAT3. In vivo experiments further verified that LINC00858 enhanced the tumorigenicity of colon cancer cells in vivo by regulating the RAD21/PCNP/STAT3/5 axis. It indicated the promoting role of LINC00858 in colon cancer progression though activating PCNP-mediated STAT3/5 pathway by recruiting RAD21.